Desegregation, Minimum Competency Testing, and the Origins of Accountability: North Carolina and the Nation. Issue 1 (February 2015) - Baker, Scott
Abstract : During the long history of the Civil Rights Movement, public education was a significant battleground in the struggle for racial equality. As the courts ordered officials to dismantle a system of educational apartheid, whites resisted, bringing blacks and whites together in ways that disillusioned many African Americans. Hoping to transcend what he called "the trauma of desegregation, " in 1977, North Carolina Governor James B. Hunt proposed that all students be required to pass a minimum competency test (MCT) to receive a high school diploma. Hunt was part of a generation of moderate New South politicians who crafted a new racially neutral educational discourse that emphasized accountability and achievement rather than equality and access. Capitalizing on the perception that the quality of education had declined, these New South moderates built biracial coalitions that established high school MCTs in every southern state by 1986, replacing a civil rights agenda of opportunity with an accountability agenda of individual student responsibility.